Bubble evolution mechanism and stress-induced crystallization in low-temperature silicon wafer bonding based on a thin intermediate amorphous Ge layer. (13th September 2017) - Ke, Shaoying; Lin, Shaoming; Ye, Yujie; Mao, Danfeng; Huang, Wei; Xu, Jianfang; Li, Cheng; Chen, Songyan
Abstract: The dependence of the morphology and crystallinity of an amorphous Ge (a-Ge) interlayer between two Si wafers on the annealing temperature is identified to understand the bubble evolution mechanism. The effect of a-Ge layer thickness on the bubble density and size at different annealing temperatures is also clearly clarified. It suggests that the bubble density is significantly affected by the crystallinity and thickness of the a-Ge layer. With the increase of the crystallinity and thickness of the a-Ge layer, the bubble density decreases. It is important that a near-bubble-free Ge interface, which is also an oxide-free interface, is achieved when the bonded Si wafers (a-Ge layer thickness  ⩾  20 nm) are annealed at 400 °C. Furthermore, the crystallization temperature of the a-Ge between the bonded Si wafers is lower than that on a Si substrate alone and the Ge grains firstly form at the Ge/Ge bonded interface, rather than the Ge/Si interface. We believe that the stress-induced crystallization of a-Ge film and the intermixing of Ge atoms at the Ge/Ge interface can be responsible for this feature.